Description of a new species of the genus Zodarion Walckenaer, 1826 (Araneae, Zodariidae) from Algeria - Bouseksou, Samira; Abrous-Kherbouche, Ourida; Bosmans, Robert; Beladjal, Lynda (Zootaxa, 2021)
A new species of the genus Zodarion Walckenaer, 1826 is described based on material collected in different regions in Algeria. Morphological, diagnostic characters and illustrations of the genitalia of both sexes are presented. The samples reveal different phenological activities for males and females, and that the species occurs in agro-ecosystem habitats.